Thermal Characteristics of InGaN/GaN Flip-Chip Light Emitting Diodes with Diamond-Like Carbon Heat-Spreading Layers - Pai-Yang Tsai; Hou-Kuei Huang; Chien-Min Sung; Ming-Chi Kan; Yeong-Her Wang (International Journal of Photoenergy)
The temperature-dependent optical, electrical, and thermal properties of flip-chip light emitting diodes (FCLEDs) with diamond-like carbon (DLC) heat-spreading layers were investigated. On the basis of the measured results in the 20°C to 100°C temperature range, a significant performance improvement can be achieved for FCLEDs with DLC heat-spreading layers (DLC-FCLED) compared with FCLEDs without DLC heat-spreading layers (non-DLC-FCLED). The external quantum efficiency (EQE) of the DLC-FCLED improves by 9% at an injection current of 1000 mA and a temperature of 100°C. The forward voltage and spectra variations are smaller than those of non-DLC-FCLEDs. The DLC-FCLED provides high efficiency and high stability performance for high-power and high-temperature applications.